2005
DOI: 10.1007/s00704-004-0117-9
|View full text |Cite
|
Sign up to set email alerts
|

BUBBLE – an Urban Boundary Layer Meteorology Project

Abstract: The Basel UrBan Boundary Layer Experiment (BUBBLE) was a year-long experimental effort to investigate in detail the boundary layer structure in the City of Basel, Switzerland. At several sites over different surface types (urban, suburban and rural reference) towers up to at least twice the main obstacle height provided turbulence observations at many levels. In addition, a Wind Profiler and a Lidar near the city center were profiling the entire lower troposphere. During an intensive observation period (IOP) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
225
2
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(246 citation statements)
references
References 46 publications
10
225
2
9
Order By: Relevance
“…The first recorded evapotranspiration measurements in urban areas based on this method were performed by Grimmond et al (1993) in Sacramento (USA) and Grimmond and Oke (1995) as comparative energy balance studies in four North American cities. Many other studies followed, performed especially in cities located at mid-latitudes, such as Christchurch (SpronkenSmith, 2002), Basel (Christen and Vogt, 2004;Rotach et al, 2005) and Łódź (Offerle et al 2006a(Offerle et al , 2006b). Meanwhile, a large number of investigations has been conducted in subtropical cities [e.g., Los Angeles (Grimmond et al, 1996), Mexico City (Barradas et al, 1999), Marseille (Grimmond et al, 2004), Tokyo (Moriwaki 144 A. GOLDBACH AND W. KUTTLER and Kanda, 2004), Ouagadougou (Burkina Faso; Offerle et al, 2005), Miami (Newton et al, 2007) and Cairo (Frey et al, 2011)] and in cities located at high latitudes [e.g., Edinburgh (Nemitz et al, 2002) and Helsinki (Vesala et al, 2008)].…”
Section: Introductionmentioning
confidence: 99%
“…The first recorded evapotranspiration measurements in urban areas based on this method were performed by Grimmond et al (1993) in Sacramento (USA) and Grimmond and Oke (1995) as comparative energy balance studies in four North American cities. Many other studies followed, performed especially in cities located at mid-latitudes, such as Christchurch (SpronkenSmith, 2002), Basel (Christen and Vogt, 2004;Rotach et al, 2005) and Łódź (Offerle et al 2006a(Offerle et al , 2006b). Meanwhile, a large number of investigations has been conducted in subtropical cities [e.g., Los Angeles (Grimmond et al, 1996), Mexico City (Barradas et al, 1999), Marseille (Grimmond et al, 2004), Tokyo (Moriwaki 144 A. GOLDBACH AND W. KUTTLER and Kanda, 2004), Ouagadougou (Burkina Faso; Offerle et al, 2005), Miami (Newton et al, 2007) and Cairo (Frey et al, 2011)] and in cities located at high latitudes [e.g., Edinburgh (Nemitz et al, 2002) and Helsinki (Vesala et al, 2008)].…”
Section: Introductionmentioning
confidence: 99%
“…The index ratio of CTRL is 6. Observation by Rotach et al (2005) indicated that maximum SH were about 300 W m 2 to 400 W m 2 in midsummer at Basel, Switzerland.…”
Section: Sensitivity Experiments For Thermal Effectmentioning
confidence: 99%
“…However, we do not focus on the quantitative estimation of the urban heat flux but on the relation between the urban shallow clouds and the contrast of heat flux, so that we chose the simple urban expression, which allows to easily control sensible heat flux in the urban area. We are going to clarify the relation between cloud and heat flux by sensitivity experiments that cover the range of urban heat fluxes obtained by the past studies (Kusaka et al 2001;Rotach et al 2005). In the sensitivity experiments, the heat contrast between the urban and the rural areas is controlled by the soil moisture at the urban grid points, which is set to 75%, 85%, and 100% for Cases U75, U85, and N00, respectively.…”
Section: Numerical Model Designmentioning
confidence: 99%
“…As part of a COST Action to examine the application of meteorology to urban air pollution problems, particular attention was paid to estimating airflow in this layer (Fisher et al 2005). Rotach et al (2005) suggest that the friction velocity at any height ( ) ( * z u ) within the RSL above the displacement height (that is, from d to z*) may be parameterised against the value at the top of the RSL (which may be obtained from the log profile), This COST approach was evaluated using wind observations acquired as part of the Basel UrBan Boundary Layer Experiment (BUBBLE) ), which included instruments located within both urban and rural settings. The results showed that eq.…”
Section: Literature Reviewmentioning
confidence: 99%